Study of Entrepreneurial Values in Social Entrepreneur: A Case Study on Social Enterprise Misteripang - Nuraida, Siti; Fauziyah, Azizah; Rachmani, Nizza Nadya (Universitas Pendidikan Indonesia, 2023)
The purpose of the study to explain study of entrepreneurial values in social enterprise Misteripang. This research is a descriptive study with a qualitative approach that aims to examine the entrepreneurial values that exist in the Social Entrepreneur Misteripang. The variables in this study are entrepreneurial values in the Social Entrepreneur Misteripang which consist of being independent, creative, risk-taking, action-oriented, leadership and hard work. The participant or subject of this research is the owner of the Misteripang. Methods of data collection using in-depth interviews, documentation and literature study. The results of this study explain that: 1) There are six main entrepreneurial values in Owner Misteripang, namely independent, creative, risk-taking, action-oriented, leadership, and hard work. 2) Finding new entrepreneurial values from Misteripang entrepreneur, namely cooperation and communicativeness. 3) Entrepreneurial values that need to be improved are action-oriented.